Indian gods, heroes, and mythology - Gagne, Tammy (Gods, heroes, and mythology., 2019)
Highlights Indian gods, goddesses, and myths that influenced the belief system of the Indian culture. Includes text-related questions, resources for further information, a glossary, and color photographs.